(untitled) (Marketing Journal, 2025)
In todayʼs global economic landscape, competitiveness has become a strategic factor for industrial enterprises. The integration of advanced technologies such as Artificial Intelligence, Big Data analytics, automation, and the Internet of Things into manufacturing processes enables companies to achieve not only operational efficiency but also strategic advantages. This paper examines the implementation of intelligent management systems in industrial enterprises, explores how they contribute to competitive advantage, and analyzes the challenges faced during this transition. 335 Practical approaches are reviewed using the case of Uzbekistanʼs industrial sector, with comparisons to leading international practices.